Nicotinamide Phosphoribosyltransferase‐elevated NAD+ biosynthesis prevents muscle disuse atrophy by reversing mitochondrial dysfunction. Issue 2 (2nd March 2023) - Zhang, Yao; Wang, Yingming; Lu, Shuai; Zhong, Rui; Liu, Zhilin; Zhao, Qichun; Wang, Chongyang
Abstract: Background: It is well known that muscle disuse atrophy is associated with mitochondrial dysfunction, which is implicated in reduced nicotinamide adenine dinucleotide (NAD + ) levels. Nicotinamide phosphoribosyltransferase (NAMPT), a rate‐limiting enzyme in NAD + biosynthesis, may serve as a novel strategy to treat muscle disuse atrophy by reversing mitochondrial dysfunction. Methods: To investigate the effects of NAMPT on the prevention of disuse atrophy of skeletal muscles predominantly composed of slow‐twitch (type I) or fast‐twitch (type II) fibres, rabbit models of rotator cuff tear‐induced supraspinatus muscle atrophy and anterior cruciate ligament (ACL) transection‐induced extensor digitorum longus (EDL) atrophy were established and then administered NAMPT therapy. Muscle mass, fibre cross‐sectional area (CSA), fibre type, fatty infiltration, western blot, and mitochondrial function were assayed to analyse the effects and molecular mechanisms of NAMPT in preventing muscle disuse atrophy. Results: Acute disuse of the supraspinatus muscle exhibited significant loss of mass (8.86 ± 0.25 to 5.10 ± 0.79 g; P < 0.001) and decreased fibre CSA (3939.6 ± 136.1 to 2773.4 ± 217.6 μm 2, P < 0.001), which were reversed by NAMPT (muscle mass 6.17 ± 0.54 g, P = 0.0033; fibre CSA, 3219.8 ± 289.4 μm 2, P = 0.0018). Disuse‐induced impairment of mitochondrial function were significantly improved by NAMPT, including citrate synthase activity (40.8 ± 6.3 to 50.5 ± 5.6 nmol/min/mg, P = 0.0043), and NAD + biosynthesis (279.9 ± 48.7 to 392.2 ± 43.2 pmol/mg, P = 0.0023). Western blot revealed that NAMPT increases NAD + levels by activating NAMPT‐dependent NAD + salvage synthesis pathway. In supraspinatus muscle atrophy due to chronic disuse, a combination of NAMPT injection and repair surgery was more effective than repair in reversing muscle atrophy. Although the predominant composition of EDL muscle is fast‐twitch (type II) fibre type that differ from supraspinatus muscle, its mitochondrial function and NAD + levels are also susceptible to disuse. Similar to the supraspinatus muscle, NAMPT‐elevated NAD + biosynthesis was also efficient in preventing EDL disuse atrophy by reversing mitochondrial dysfunction. Conclusions: NAMPT‐elevated NAD + biosynthesis can prevent disuse atrophy of skeletal muscles that predominantly composed with either slow‐twitch (type I) or fast‐twitch (type II) fibres by reversing mitochondrial dysfunction.